What have we learned studying income inequality and population health? - Ross, Nancy A. (Ottawa, 2004)
"Epidemiologists and social scientists around the world have long been interested in studying the relationship between income distribution and health. What Have We Learned Studying Income Inequality and Population Health? synthesizes the research on income inequality and health. This report reviews the chronology of studies on income inequality and health, explores some of the differences between countries and examines research gaps."